Application and Optimization of MIMO Communication in Wide Area Monitoring Systems - Recioui , Abdelmadjid; Grainat , Youcef (International Journal of Data Science, 2020)
Multiple-Input Multiple-Output (MIMO) technology uses a multitude of antennas at both transmitter and receiver to transfer a larger data mount simultaneously. It is the key technology in the 4th and 5th communication system generations. In this work, the use of MIMO technology to enhance the data transfer in terms of completeness, correctness and latency in Wide Area Monitoring Systems (WAMS) is envisaged. To further enhance the system, optimization is done to design the communication system in terms of physical layout. A comparison with the state of art technologies is done to highlight how the adoption of the MIMO technology would enhance the data transfer within the smart grid.